An investigation into the journalistic identities of news workers at the state owned Lentsoe La Basotho/Lesotho Today Newspaper - Kotele, Mothepane (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2010)
Informed by the political economy framework and the public service role of media in democracy, the main objective of the study was to use in-depth semi-structured interviews to understand news-workers' professional journalistic identities in relation to their status as government employees and the understanding of their public service role as outlined in the paper's mission statement. The main interest was to understand the complexity of negotiating these role identities. Through reference to the theories of journalism professionalism, the study highlighted the extent to which news-workers in the small newsroom of Lentsoe la Basotho/Lesotho Today see themselves as public service journalists in a democratic country. The interest was borne partly out of the views of the paper's critics who see it as not serving the public but rather promoting the activities and policies of the government of the day, thus falling short of its democratic role. The contention of the study was that as a public service newspaper, the paper should have news-workers who do impartial journalism and reflect the public's right to know in their reporting. The findings of the study suggests that news-workers at Lentsoe la Basotho/Lesotho Today continuously have to strive to negotiate the potential conflict between being a professional and working for a government-controlled newspaper. While they sometimes lay claim to being journalists, the reality is that in their political coverage they end up adopting the role of government mouthpieces.
Keywords: Lentsoe La Basotho/Lesotho Today; Mass media -- Economic aspects -- Lesotho; Mass media -- Social aspects -- Lesotho; Mass media -- Employees; Journalists -- Lesotho; Sotho newspapers; Journalistic ethics -- Lesotho